Climate Resilience, Agroforestry and REDD+ Governance in the Midst of Indonesia's Climate Change - Vika Fransisca (International Journal of Social Research, 2025)
Climate change in Indonesia presents serious challenges due to deforestation, land degradation, and increasing greenhouse gas emissions from the forestry sector. As a country with the third largest tropical forest in the world, Indonesia needs an adaptive strategy that is not only able to reduce emissions, but also strengthen people's welfare. Agroforestry is considered a potential solution that supports the implementation of REDD+ schemes to achieve the 2030 NDC targets. This study aims to analyze the role of agroforestry in strengthening climate resilience while exploring its integration with REDD+ governance in Indonesia. A qualitative approach with a case study design was used through in-depth interviews, participatory observations, and documentation studies in forest villages in Kalimantan and Sumatra. The data was analyzed using thematic analysis techniques with source triangulation to ensure the validity of the findings. Research has found that agroforestry systems are able to improve soil quality, absorb higher carbon than monocultures, and support farmer income diversification by up to 20–30%. The integration of agroforestry with REDD+ governance also increases community participation and strengthens local institutions. However, limited funding, technical capacity, and governance transparency remain challenges. The study's recommendations include strengthening carbon incentives, building community capacity, and more participatory and equitable management of REDD+. Agroforestry has proven to function not only as a technical mitigation strategy, but also as a socio-economic instrument that strengthens climate resilience and supports the sustainability of REDD+ governance in Indonesia.